PENGARUH BRAND CHARACTERISTIC DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA MATAHARI DEPARTMENT STORE BENGKULU - Hendri, Oon Hendri; Subandrio, Subandrio (UM. Bengkulu, 2024)
The problem with purchasing decisions is that consumers do not always go through all stages of a purchasing decision or carry them out. This entire process is usually carried out in certain situations, for example for the first purchase and/or purchasing goods whose price or value is relatively high. The purpose of this research is to determine the influence of brand characteristics and price on purchasing decisions at Matahari Department Store, Bengkulu City. This research is a type of quantitative research, namely systematic scientific research on parts and phenomena and the causality of their relationships. The population in this study were all consumer buyers at Matahari Department Store, Bengkulu City with a sample of 55 people. The data collection techniques are documentation, observation and questionnaires. In this research, researchers will research descriptively and also inferentially using SPSS The results of the research are that Brand characteristic (X1) has a positive and significant effect on purchasing decisions (Y) at Matahari Department Store. Price (X2) influences purchasing decisions (Y) at Matahari Department Store. Brand characteristics (X1) and price (X2) influence purchasing decisions (Y) at Matahari Department Store. Keywords : Brand Characteristics, Price, Purchasing Decisions.